ANALYSIS ON THE POTENTIAL OF KERTA SEMAYA SAMINAYA TO ENTER THE GERMAN MARKET (The Indonesian Journal of Business Administration, 2019)
PT. Solarens Ledindo for the past five years focused its business on the sale of public solar street lighting products which are widely used to supply the needs of infrastructure development projects in Indonesia. Therefore the company becomes dependent on the existence of development projects from the government to be able to run its business. The dependency causes the company to experience high fluctuations in the revenue it can get. For this reason, an alternative market is needed for companies to enter. The big potential is the Highbay lighting products which are widely used in the industry. The challenge faced by entering this product market is the high number of Highbay lighting products from China that have lower prices than the products offered by PT. Solarens Ledindo. Financial Feasibility Study is needed to find out the possibility of the company to enter the Highbay product market. The methodology used in this research is to find out the business issue first, then find out the business situation of the Highbay lighting industry through internal analysis using financial ratios and external analysis using PESTEL and Five Forces. Then do the calculation of the Financial Projection and Financial Feasiblity Study of the project.Keywords:  Feasibility Study, Highbay, PT. Solarens Ledindo, CAPM, Risk Management